Development of the entrepreneurial career: Identification of profiles, skills and needs - Suárez Ortega, Magdalena; Sánchez-García, Mª Fe; Soto-González, María Dolores (Revista Complutense de Educación, 2020)
Within the specific framework of vocational training and guidance of young people and adults, entrepreneurship is considered as a possible transition that occurs in the professional / work the structural precarization of people, which implies for the construction and reorientation of professional and life projects. The objective of this article is to analyze the motivations and career determinants of the people who carry out an entrepreneurial activity, identifying profiles and needs about the way in which they articulate their various vital-professional roles. For this purpose, the questionnaire on Motivation and conditioners of entrepreneurship career (MCCE) was designed and applied, determining its psychometric characteristics (n = 248 entrepreneurs in Spain): content validity (expert review), construct validity (exploratory factor analysis) and internal consistency (Cronbach's alpha = .79), checking the suitability and relevance of the instrument. The results show a marked satisfaction with respect to their professional trajectories, while the existence of conflicts for personal-professional conciliation. Business advice needs are differentiated from career guidance needs. The presence of a variety of motivations to undertake is identified, finding, through cluster analysis three notable profiles based on the factors found and the sociodemographic variables. The model obtained its implications for the design of training and orientation actions for entrepreneurs are discussed.
Keywords: vocational training and guidance; entrepreneurial career; guidance needs; motivation; skills